Designing an Appropriate Structural Model for Predicting Child Abuse Based on Personality Traits and Parental Bonding - Bahmani, Tahmineh; Nasseri, Naziasadat; Fariborzi, Elham (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the structural model for predicting child abuse based on personality traits, and parental bonding. Method: The study was descriptive-correlational, and the statistical population consisted of 248594 high school girls in Mashhad in 2017-2019, and 384 girls and their parents were selected using multi-stage random sampling. The research tools included the personality trait questionnaire by McCrae and Costa (1989), the Parental Bonding Instrument (PBI) by Gordon Parker (1979), and the Childhood Trauma Questionnaire (CTQ) by Bernstein et al. (2003). The data were analyzed using correlation coefficients, and the path analysis structural model. Results: The results indicated that designing a structural model for predicting child abuse based on parental personality traits, and parental bonding was consistent with the theoretical model and had a good fit. The results also indicated a significant positive correlation between parental bonding in care and emotional support with personality traits, namely extraversion, conscientiousness, agreeableness, and responsibility (P=0.01), and a significant negative correlation with emotional harassment, physical harassment, sexual harassment, neglect, and malnutrition (P=0.01). Furthermore, there was a direct significant effect of parental bonding in care, emotional support, parents' personality traits, the contribution of neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness on child abuse (P=0.01). Conclusion: The study indicated the need to investigate personality traits and strategies of parents to deal with children, as well as the importance of parental bonding to know more parents and develop appropriate treatment programs.